What do health consumers want to know about childhood vaccination? An evaluation of data from an Australian medicines call centre - Marnix Mus; Sanne Kreijkamp‐Kaspers; Treasure McGuire; Laura Deckx; Mieke van Driel (Elsevier, 2017)
Abstract Objectives: Immunisation is crucial to population health. This study aimed to identify the information needs and concerns of health consumers regarding childhood vaccination. Methods: We analysed 1,342 calls concerning childhood vaccination to an Australian pharmacist‐operated medicines call centre (MCC). Data were available from September 2002 until June 2010. We identified key themes and compared these for callers from high and low immunisation coverage areas. Results: Most calls related to safety concerns (60.4%), with many questions about vaccine constituents (31.6%). In low immunisation areas, a higher level of concern persisted about vaccine preservatives (mercury and thiomersal) despite their removal from vaccines in 2000. Of specific vaccines, the measles, mumps and rubella vaccine raised most questions (29.9%). Common motivations to call the MCC were 'inadequate information' (54%), 'second opinion' (21%) 'conflicting information' (9%) and 'worrying symptom' (6%). Conclusion and implications: The consistent number of vaccine‐related calls, particularly about safety, demonstrates an information gap that can contribute to vaccination hesitancy. Health professionals need to know their local immunisation rate and associated carer concerns, to proactively address these information‐related barriers to vaccination.